Writing windows WDM Device Drivers. Covers NT4, Win 98, and Win 2000 - Cant, Chris
Master the new Windows Driver Model (WDM) common to Windows 98 and Windows 2000. You get theory, instruction and practice in driver development, installation and debugging. Addresses hardware and software interface issues, driver types, and a description of the new